2022
DOI: 10.3126/paj.v5i1.45044
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Profitability of Commercial Banks: Evidence from Nepali Banking Sector

Abstract: This article aims to observe the various aspects shaping commercial bank profitability in Nepal. As determining factors, bank related and external macroeconomic variables that influence bank profitability were taken into account. A set of balanced panel data containing 13 Nepali commercial banks for 12-year period (2009-2020) with 156 observations was employed for analysis. Descriptive statistics and Pearson's correlation analysis were employed to measure the status and explore the relationship between indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Similarly, Gwachha [34] discovered a robust positive effect of the size of assets, deposit ratio, market size, and interest rate on the performance of banks and a significant adverse effect on loans portfolio. Likewise, Gurung and Gurung [35] found the positive influence of the loan ratio on the profitability and net interest margin of banks operating in Nepal.…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, Gwachha [34] discovered a robust positive effect of the size of assets, deposit ratio, market size, and interest rate on the performance of banks and a significant adverse effect on loans portfolio. Likewise, Gurung and Gurung [35] found the positive influence of the loan ratio on the profitability and net interest margin of banks operating in Nepal.…”
Section: Introductionmentioning
confidence: 91%
“…Operating expenses, leverage, liquidity and market capitalization have positive significant influence to return on equity in Nepalese commercial banks. Gurung and Gurung (2022) conducted research to identify the impact of bank related and external macroeconomic variables on profitability of Nepalese commercial banks and found that loan to deposit ratio and growth of gross domestic product have positive significant influence to the return on assets and net interest margin. However, non-performing assets has significant negative influence to the return on equity, but it has weakly negative impact to the return on assets.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It is ability of delivering quality product and services with minimum input of resources (Pradhan & Sah 2023). It is a right combination of input resources to enhance the productivity and value of any business operation, while driving down the cost of routine operations to a desired level (Gurung & Gurung, 2022). If the bank provides quality bank services at lower possible cost which is called operating efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…However, capital adequacy ratio is insignificant for the banks' performance. Gurung and Gurung (2022) observed the factors determining profitability of Nepalese commercial banks the study found that loan to deposit ratio and GDP have a positive and significant impact on return on assets. Further, the study also showed non-performing loan and capital adequacy ratio have a negative and significant impact on return on equity.…”
Section: Introductionmentioning
confidence: 99%